PENGARUH LOGISTIC SERVICE QUALITY PADA THE BEST MARKETPLACE DI INDONESIA - NABIILAH, NOVA ALIFFIA; Rahayu, Siti; Widjaja, Fitri Novika (STKIP Persada Khatulistiwa Sintang, 2025)
In the era of growing digitalization, the retail world is experiencing significant generational changes, the world of markets and logistics has a very close influence in influencing customer satisfaction. This research aims to analyze the influence of logistics service quality regarding factors that influence customer satisfaction, loyalty and future purchases on buying and selling platforms. Using the Smart PLS application 4. Factors tested include timeliness, order conditions, order accuracy, information quality, order availability, order procedures, and order guarantee quality. The research results show that timeliness, quality and ordering procedures have a positive effect on customer satisfaction, increasing purchase intentions and loyalty in the future period. Meanwhile, ordering conditions, ordering accuracy and service quality do not have a positive effect. This research suggests the market should focus more on on-time delivery, accurate information, and a smooth ordering process to increase customer satisfaction, loyalty, and future purchase intent.